Policies and institutions: removing barriers to rural-urban exchange - Garrett, James L. (International Food Policy Research Institute, 2005)
Urbanization, trade liberalization, agroindustrialization, and the rise of supermarkets are among the trends providing farmers in poor countries with new opportunities to participate in local and global markets. For farmers to benefit from these changes, however, they must have the resources, skills, and information needed to access and participate in these markets. In addition, rural, urban, and export markets must themselves be integrated.